Yoga, Dance, Team Sports, or Individual Sports: Does the Type of Exercise Matter? An Online Study Investigating the Relationships Between Different Types of Exercise, Body Image, and Well-Being in Regular Exercise Practitioners - Marschin, Verena; Herbert, Cornelia (Frontiers in Psychology, 2021)
Physical activity, specifically exercising, has been suggested to improve body image, mental health and well-being. With respect to body image, previous findings highlight a general benefit of exercise. This study investigates whether the relationship between exercising and body image varies with the type of exercise that individuals preferentially and regularly engage in. In addition, physical efficacy was explored as a potential psychological mediator between type of exercise and body image. Using a cross-sectional design, healthy regular exercise practitioners of yoga, ballroom dance, team or individual sports as well as healthy adults reporting no regular exercising were surveyed. Body image and its different facets were assessed by a set of standardized self-report questionnaires, covering perceptual, cognitive, and affective body image dimensions particularly related to negative body image. In addition, participants were questioned with regard to mental health. Participants were 270 healthy adults. Descriptive statistics, measures of variance (ANOVA) and multiple linear regression analysis with orthogonal contrasts were performed to investigate differences between the different exercise and non-exercise groups in the variables of interest. In line with the hypotheses and previous findings, the statistic comparisons revealed that body dissatisfaction (as one important factor of negative body image) was most pronounced in the non-exercise group compared to all exercise groups (contrast: no-exercise versus exercise (all groups taken together)). Physical efficacy, as assessed with a standardized questionnaire, mediated the difference between type of exercise (using contrasts) and body image including perceptual, cognitive and affective body image dimensions. The findings shed light on so far less systematically investigated questions regarding the relationship between types of exercise, like yoga and ballroom dance, and body image. The results underscore the relevance of considering possible influencing factors in exercise research, such as the perception of one’s physical efficacy as a mediator of this relationship.